Toxic effects of acute exposure to polystyrene microplastics and nanoplastics on the model insect, silkworm Bombyx mori. (15th September 2021) - Muhammad, Abrar; Zhou, Xiaoxia; He, Jintao; Zhang, Nan; Shen, Xiaoqiang; Sun, Chao; Yan, Bing; Shao, Yongqi
Abstract: Microplastics and nanoplastics (MPs and NPs, respectively) are major contaminants of environmental concern due to their potentially detrimental effects on aquatic and terrestrial ecosystems. However, little is known about their potential toxicity in terrestrial organisms. Here, we used the model insect silkworm ( Bombyx mori ) to evaluate the potential hazardous effects of acute exposure (72 h) to polystyrene (PS) MPs and NPs at physiological, molecular, and biochemical levels as well as their impact on pathogen infection. Our results revealed no significant changes in larval body mass or survival. Nevertheless, exposure led to significant alterations in the expression of immunity-related genes ( Cecropin A, Lysozyme, SOD, and GST ) and antioxidant-mediated protective response (SOD, GST, and CAT enzymes) which differed in the PS-MP and PS-NP groups. Interestingly, PS-MPs induced a stronger immune response (higher expressions of Lysozyme, SOD, and GST genes along with increased activities of SOD, GST, and CAT enzymes) while the PS-NP response was more that of an inhibitory nature (decreased SOD activity and expression). As a result, upon infection with the natural pathogen Serratia marcescens Bm1, the PS-MP-exposed individuals survived the infection better whereas, PS-NP-exposed individuals exhibited significantly higher mortality. Thus, we infer that PS-MPs/NPs present ecological toxicity, which is closely related to their size, and that their exposure may render the organisms vulnerable or confer resistance to pathogen infections and ecotoxicants. Given the suitability of silkworm as a model organism, this study may promote its application for further investigation of the mechanism of adverse outcome pathways and in studies on bio-nano interactions. Graphical abstract: Image 1 Highlights: Bioaccumulation occurred in the gut tissues for the PS-NPs but not for PS-MPs. Exposure caused alterations at physiological, biochemical, and molecular levels. PS-MPs induced a stronger immune response and hosts better survived the infection. PS-NPs exposure suppressed the immune response and rendered the host vulnerable. Silkworm is a suitable model to evaluate hazardous effects of plastic pollutants.